A study on acceptance of new retirement age policy among employees in Kota Kinabalu / Faranimah Amir Ali and Ramli Muhamma Tahir - Amir Ali, Faranimah; Muhamma Tahir, Ramli (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2013)
According to Law of Malaysia Act 753, retirement can be defined as the termination of contract of service of an employee on the ground of age. The new retirement age policy in Malaysia requires employees to retire at 60 which before this at 58 and 55. The purpose of this study is to determine whether the people specifically employees accept the increase of the age of retirement to 60 or not. This study was conducted with a survey by distribution of self-developed questionnaires. Based on this study, most employees have a moderate level of acceptance towards the new retirement age policies 2012. However, the results were skewed more towards positively accept the policy. Moreover, in general, finding also revealed that, majority of the respondents prefer 55 years old as the ideal age for retirement. Though this study cannot be generalize nor can the results fully representing the collective opinions across all Malaysian on such a topic, yet this study was able to show that there are numerous dimension of concerned from demographically, economically and socially points of views that would like to be given the opportunity to be examined.